The effectiveness & efficiency of e-aedes framework based on GIS - Ilham, Muhammad; Mohamed, Ibrahim (International Journal of Engineering and Technology, 2019)
An effective and efficient management of information can be achieved through the use of information technology. The emergence of dengue virus is associated with uncontrollable breeding of mosquito, and the poor level of cleanliness of the environment. The prevention of mosquito breeding and control have been carried in recent years, which rely on the eradication, the case of Dengue Fever and Dengue Hemorrhagic Fever (DD & DDB) still exist. To hindrance the case of DD & DDB, prevention is the key factor in controlling the spread of the disease and the breeding of mosquito-borne. To prevent the spread of disease and mosquito breeding a quick and appropriate information is needed to locate the areas that have the potential breed of mosquito. The objective of this study is to Collecting knowledge through a literature review and expert understanding of Aedes / Dengue mosquitoes and equipped with a ready, effective and efficient of information. This research uses qualitative and quantitative methodology. This framework is verified through readiness, effectiveness and efficiency. This research shows positive results, particularly for the effectiveness and efficiency.Â Â